AN INNER TRIP: WOMEN AND NATURE IN MARGARET ATWOOD’S SURFACING - Serpa, Luciana Labatti Teixeira (Em Tese, 2004)
This article studies the relationship between women and nature by analyzing nature as a possible means for women’s self-discovery in Margaret Atwood’s novel Surfacing, having as a theoretical reference notions of contemporary ecofeminist literary theory.